Exercise-Induced Neuroplasticity: Adaptive Mechanisms and Preventive Potential in Neurodegenerative Disorders - Masab Mansoor; Andrew Ibrahim; Ali Hamide; Tyler Tran; Ethan Candreva; Jad Baltaji (Physiologia)
Background/Objectives: Neurodegenerative diseases represent a growing global health challenge with limited therapeutic options. Physical exercise has emerged as a promising non-pharmacological intervention with potential neuroprotective effects. This narrative review examines the mechanisms through which exercise induces neuroplasticity and their implications for neurodegenerative disease prevention. Methods: We synthesized evidence from molecular, animal, and human studies on exercise-induced neuroplasticity and neurodegenerative disease prevention through a comprehensive literature review. Results: Exercise enhances neuroplasticity through multiple pathways: (1) neurotrophic signaling (BDNF, IGF-1, VEGF), (2) neuroendocrine regulation, (3) epigenetic modifications, and (4) metabolic pathway optimization. These molecular changes support structural adaptations including hippocampal neurogenesis, enhanced synaptic plasticity, improved cerebrovascular function, and optimized brain network connectivity. Exercise directly impacts pathological features of neurodegenerative diseases by reducing protein aggregation, attenuating excitotoxicity and oxidative stress, and enhancing mitochondrial function. Clinical evidence consistently demonstrates associations between physical activity and reduced neurodegenerative risk, with intervention studies supporting causal benefits on cognitive function and brain structure. Conclusions: Exercise represents a multi-target intervention addressing several pathological mechanisms simultaneously across various neurodegenerative conditions. Its accessibility, minimal side effects, and multiple health benefits position it as a promising preventive strategy. Future research should focus on understanding individual response variability, developing sensitive biomarkers, and creating personalized exercise prescriptions for optimal neuroprotection.